Effective Adoption of Striga Control Technologies in Maize by Association and Non-Association Farmers in Bungoma County, Kenya - Livondo , Julius Luhaz (African Journal of Education,Science and Technology (AJEST), 2018)
Striga species also known as witchweeds decimate agriculture in most parts of Africa, attacking the major cereal grains and legumes, and halving the already very low yields of subsistence farmers in Kenya, Bungoma County in particular. Several researchers have provided promising technologies and a range of potential control options for striga based on the fundamental biology of the parasite host associations, for dealing with this scourge. The question however still remains on whether these methods have been effective in the control of the striga weed. This paper thus describes and discusses some of the control options with a focus on technology adoption. It seeks to establish how effective the adoption of striga technology is in control of the striga among association and non-association farmers in Bungoma County, Kenya. The study employed a survey approach on a sample size determined by proportionate sampling method of small scale farmers in Bungoma County. A sample size of 110 respondents from Farmers Associations and 100 non-FAs farmers was selected using snowball sampling method. Questionnaires and interview schedules were used to collect data from the Farmers in Associations (FAs) and Non FAs farmers. Analysis of the collected data was done using quantitative statistics which enabled computation of means, percentages and standard deviations. A t-test was also performed and a hypothesis tested at 5% significant level. The study identified use of herbicides, seed selection, proper land preparation, compost fertilizer and proper weeding as weed control methods in order of preference. The findings of this study hoped to help extension officers in Bungoma County in providing information on the preferred forms of striga control strategies in maize production.